Measuring consumer knowledge of life insurance products in South Africa - M. Ramchander (South African Journal of Business Management, 2016)
The financial services industry is characterized by product suppliers having more information than consumers regarding product features and services. The purpose of this article is to explore this information asymmetry with particular reference to the life insurance industry. Financial advisors, acting as intermediaries, are charged with the task of resolving this asymmetry through mandatory disclosures demanded by regulation. In South Africa, the Financial Services Board (FSB) monitors, regulates and supervises the financial services industry through the Financial Advisory and Intermediary Services Act of 2002 and The Code of Conduct for Financial Advisors. This paper distinguishes financial products from other products and highlights the need for disclosures regarding product features, by financial advisors. Using multistage sampling a national survey was conducted to establish whether consumers are knowledgeable of the features of basic insurance products. The findings were that consumers have a low to very low level of understanding of the features of basic insurance products. The study makes an important contribution to insurers' understanding of consumers' knowledge regarding the features of basic life insurance products. Furthermore, the findings would also contribute to insurersunderstanding the level to which intermediaries resolve the information asymmetry between product suppliers and consumers.
Keywords: 650